Economic Contributions of Florida's Agricultural, Natural Resource, and Food and Kindred Product Manufacturing, Distribution, and Service Industries in 2007 - Alan W. Hodges; Mohammad Rahmani (EDIS)
FE800, a 28-page illustrated report by Alan W. Hodges and Mohammad Rahmani, provides estimates of the agricultural, natural resource, and food and kindred product manufacturing, distribution, and service industries’ economic contributions to Florida in 2007, updating a previous study for 2006. Includes references. Published by the UF Department of Food and Resource Economics, April 2009.